FAKTOR-FAKTOR PENDORONG PENINGKATAN JUMLAH PESERTA LATIHAN MULTILATERAL NAVAL EXERCISE KOMODO (MNEK ) 2023 - Rahmaini, Rahmaini; Pertiwanggono, Benny; Alfahri, Muhammad Riziq (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The purpose of this research is to find out how Multilateral Naval Exercise Komodo (MNEK) 2023 experienced a significant increase in the number of participants compared to previous years. This research aims to identify the factors that drove the increase. Data was collected through scholarly articles, document analysis, and books. The results show that the main contributing factors include: increased international cooperation in maritime security, MNEK's reputation as a credible and effective multilateral exercise, increased maritime security threats that require multilateral cooperation, and better facilities and logistical support from the organizers. In addition, active promotion and diplomacy by the Indonesian Navy and improved bilateral and multilateral relations between participating countries also play an important role. This research provides an in-depth understanding of the dynamics of participation in multilateral military exercises and their implications for maritime security strategy